2001
DOI: 10.1038/89482
|View full text |Cite
|
Sign up to set email alerts
|

Cell-surface heparan sulfate is involved in the repulsive guidance activities of Slit2 protein

Abstract: Slit proteins are a family of secreted guidance proteins that can repel neuronal migration and axon growth via interaction with their cellular roundabout receptors (Robos). Here it was shown that Slit2-Robo-1 interactions were enhanced by cell-surface heparan sulfate. Removal of heparan sulfate decreased the affinity of Slit for Robo by about threefold. In addition, removal of cell-surface heparan sulfate by heparinase III abolished the chemorepulsive response to Slit2 normally shown by both the migrating neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
146
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(153 citation statements)
references
References 50 publications
5
146
0
Order By: Relevance
“…These two modes of action are not entirely mutually exclusive. Increasing data indicate that some axon guidance molecules also bind HS and require HS to exert their functions (Hu, 2001;Inatani et al, 2003;Kantor et al, 2004) (for review, see Lee and Chien, 2004;Holt and Dickson, 2005). Considering that axon guidance occurs in highly defined topological contexts, it is important to determine which mode of HS action is used in the function of these molecules.…”
Section: Discussionmentioning
confidence: 99%
“…These two modes of action are not entirely mutually exclusive. Increasing data indicate that some axon guidance molecules also bind HS and require HS to exert their functions (Hu, 2001;Inatani et al, 2003;Kantor et al, 2004) (for review, see Lee and Chien, 2004;Holt and Dickson, 2005). Considering that axon guidance occurs in highly defined topological contexts, it is important to determine which mode of HS action is used in the function of these molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it seems likely that a coreceptor is required to transmit SLIT binding into ROBO4 activation. In some contexts, ROBO1 may fulfill this function (5), whereas in other contexts it may be served by receptors such as a Syndecan (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…ROBO1, which binds directly to SLITs, has been shown to promote endothelial cell motility, either alone (2,6,10) or as a heterodimeric partner with ROBO4 (5,9). In contrast, ROBO4 binds SLITs at either very low affinity or not at all and likely requires a coreceptor, such as ROBO1 or a Syndecan, to signal (5,11,12). ROBO4 has been assigned the repellent functions of SLITs (7,8) and, more recently, an alternative role in countering the effects of vascular endothelial growth factor (VEGF) to provide vascular stabilization (13,14).…”
mentioning
confidence: 99%
“…Thus, biochemical experiments have shown that Slits bind the heparan sulfate proteoglycan glypican-1 (Liang et al, 1999;Ronca et al, 2001). Heparan sulfate enhances the affinity of Slit2 for Robo1 receptors in vitro, and removal of cell surface heparan sulfate by heparinase III treatment or addition of saturating amounts of heparan sulfate abolishes the repulsive activity of Slit2 toward olfactory bulb axons in explant cultures (Hu, 2001). Moreover, nervous system-specific conditional mutants for EXT1, a glycosyltransferase enzyme required for the synthesis of heparan sulfate, display guidance defects at the optic chiasm that are similar to those found in Slit1;Slit2 double mutants Inatani et al, 2003).…”
Section: Interaction Of Slit/robo Signaling With Other Moleculesmentioning
confidence: 99%